2011
DOI: 10.1177/016173461103300301
|View full text |Cite
|
Sign up to set email alerts
|

Subharmonic Contrast Microbubble Signals for Noninvasive Pressure Estimation under Static and Dynamic Flow Conditions

Abstract: Our group has proposed the concept of subharmonic aided pressure estimation (SHAPE) utilizing microbubble-based ultrasound contrast agent signals for the noninvasive estimation of hydrostatic blood pressures. An experimental system for in vitro SHAPE was constructed based on two single-element transducers assembled confocally at a 60 degree angle to each other. Changes in the first, second and subharmonic amplitudes of five different ultrasound contrast agents were measured in vitro at static hydrostatic press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
97
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 70 publications
(108 citation statements)
references
References 29 publications
11
97
0
Order By: Relevance
“…Previously, it has been shown that the subharmonic amplitude (at half the transmitting frequency) decreases linearly with increases in ambient fluid pressure and that this change is more than three times greater than either the fundamental or the second harmonic peak fluctuation (8)(9)(10)(11). This response forms the basis of a technique referred to as subharmonic aided pressure estimation (SHAPE).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, it has been shown that the subharmonic amplitude (at half the transmitting frequency) decreases linearly with increases in ambient fluid pressure and that this change is more than three times greater than either the fundamental or the second harmonic peak fluctuation (8)(9)(10)(11). This response forms the basis of a technique referred to as subharmonic aided pressure estimation (SHAPE).…”
Section: Methodsmentioning
confidence: 99%
“…(a sonographer with 26 years of scanning experience) or P.M. (a radiologist with 10 years of experience). The SHAPE mode was set to transmit four-cycle pulses at 2.5 MHz and to receive subharmonic signals at 1.25 MHz, as determined during previous optimization of the technique (11). In addition to acquiring SHAPE data, this unit also provided the ability to simultaneously display B-mode US images (at 4.0 MHz and a mechanical index of 0.32, intermittently transmitting between SHAPE pulses) and subharmonic US images (generated from the time domain of the SHAPE data) for easier US navigation and identification of the vascular structures of interest; namely, the portal and hepatic veins (20).…”
Section: Ultrasonography: Noninvasive Estimation Of Hepatic Venous Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Techniques for estimating ambient pressures using microbubbles have been proposed [6][7][8][9][10], but these techniques have yielded clinically unacceptable errors (as high as 10-15 mmHg in vitro under ideal conditions). A different approach utilizing subharmonic emissions from ultrasound contrast agents to track pressures called SHAPE (subharmonic aided pressure estimation) was proposed and validated in vitro [11,12]. Subharmonic emissions from microbubbles are a function of incident acoustic pressure and characterized into 3 stages -occurrence, growth and saturation.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this work was to evaluate the use of microbubbles to track dynamic pressures in a continuous flow environment and to develop a SHAPE application using a commercially available ultrasound scanner and an existing ultrasound contrast agent. Based on prior studies [11][12][13] Sonazoid microbubbles (GE Healthcare, Oslo, Norway; perfluorobutane gas encapsulated in a membrane of hydrogenated egg phosphatidyl serine) were selected for use in this study. Furthermore, as a proof-of-concept of the proposed technique, the noninvasive tracking of left ventricular (LV) pressures in vivo was investigated.…”
Section: Introductionmentioning
confidence: 99%